UV and Visible Light-Induced Photocatalytic Efficiency of Polyaniline/Titanium Dioxide Heterostructures - Yongqiang Fu; Marcin Janczarek (Molecules)
The concept of using polyaniline/titanium dioxide heterostructures as efficient photocatalysts is based on the synergistic effect of conducting polymer and metal oxide semiconductors. Due to inconclusive literature reports, the effect of different polyaniline/TiO2 ratios on photocatalytic activity under UV and visible light was investigated. In most papers, non-recommended dyes are used as model compounds to evaluate visible light activity. Therefore, colorless phenol was used instead of dyes in this study to clarify the real visible light-induced photocatalytic activity of polyaniline/TiO2 composites. This publication also includes a discussion of whether materials derived from bulk (non-nanostructured) polyaniline and TiO2 by the standard in situ oxidative polymerization method are suitable candidates for promising photocatalytic materials. The evaluation of photocatalytic activity was performed in both UV and visible light systems. X-ray diffraction and UV-Vis diffuse reflectance spectroscopy methods were applied to characterize the obtained samples. Obtained polyaniline (pure and in composites) was identified as emeraldine salt. In the UV system, none of the prepared samples with different polyaniline–titania ratios had activity better than reference P25 titania. It has been observed that the presence of polyaniline adversely affects the photocatalytic properties, as the polyaniline layer covering the titania surface can shield the UV light transmission by blocking the contact between the TiO2 surface and organic molecules. In the case of using visible light, no synergies have been observed between polyaniline and titania either. The photodegradation efficiencies of the most active samples were similar to those of pure polyaniline. In conclusion, in order to obtain efficient polyaniline/titania photocatalysts active in UV and/or visible light, it is necessary to take into account the morphological and surface properties of both components.